Review of approaches and methods for identifying experts in organizational research - E. M. Shironina (Вестник университета)
In scientific studies, three approaches are used to identify experts in organizational research: sociological, behavioral, and cognitive. In the sociological approach, the emphasis is on the socio-political status of a person. The behavioral approach focuses on how choices are made in situations of uncertainty. In the cognitive approach, the subject of the thought process is considered directly. The article shows the limitations of each of the approaches. Methods for identification of experts in organizational research in domestic and foreign scientific studies are given. Methods are considered: social acclamation, political influence, problem situation, personal involvement, external cues, self-ratings, past performance, knowledge tests, psychological traits. The advantages and disadvantages of each method are shown. Expert identification methods provide a set of opportunities for researchers of organization and organizational behavior, depending on the need for: expert judgment or expert knowledge; expert evaluation procedures or the product of professional activity; knowledge of a topic, a problem, highly specialized markets or representation of the interests of specific actors, groups, ideas, concepts. The author uses general logical research methods: induction, deduction, analysis, synthesis, scientific abstraction, comparison and contrasting.